Advanced Integration of Aeromagnetic, Radiometric, and Multispectral Remote Sensing Data for Structural Characterization, Hydrothermal Alteration Mapping, and Mineral Prospectivity Modeling of Lithium–Cesium–Tantalum Pegmatites and Orogenic Gold in the Bo - Gazala Yousuf Mir (PT. Radja Intercontinental Publishing, 2026)
This study employs an integrated geospatial and geophysical framework to assess the mineral prospectivity of the Borgu Area, Niger State, northwestern Nigeria, with particular emphasis on rare-metal pegmatites (lithium, beryl, and tourmaline) and orogenic gold systems. The study area is situated within the Nigerian Basement Complex of the Pan-African Mobile Belt and is predominantly underlain by granitic gneiss. Interpretation of aeromagnetic datasets reveals a well-defined NE–SW structural fabric characterized by faults, fractures, and lithological boundaries, which are interpreted as key controls on fluid migration and mineral emplacement. The Total Magnetic Intensity response is dominated by low-amplitude anomalies, indicative of magnetite-depleted felsic lithologies typically associated with Lithium–Cesium–Tantalum (LCT) pegmatite systems. Source Parameter Imaging further constrains the depth to magnetic sources to approximately 120–180 m, suggesting relatively shallow subsurface conditions favorable for exploration.Radiometric analysis delineates zones enriched in potassium and thorium, reflecting highly evolved granitic systems with potential for rare-metal mineralization. Complementary remote sensing analysis based on Landsat imagery identifies diagnostic hydrothermal alteration signatures, including iron oxide staining, clay mineral development, and silica enrichment. The integration of geophysical, radiometric, and spectral datasets within a GIS-based analytical framework enabled the systematic delineation of ten high-priority exploration targets. The combined results highlight the strong influence of lithological composition, structural architecture, and hydrothermal processes on mineralization within the Borgu basement terrain. These findings underscore the exploration potential of the area and provide a robust basis for subsequent field validation, including detailed geological mapping, geochemical surveys, and targeted ground geophysical investigations.